PENAMBAHAN EKSTRAK KULIT BUAH NAGA PADA PENGEMBANGAN PRODUK NATA DE COCO BERANTIOKSIDAN - Budi Santosa; Lorine Tantalu; Untung Sugiarti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Nata de coco is made from coconut water which is processed by fermentation using Acetobacterxylinum. The nutrients in this product are mostly cellulose fibers better known as bacterial cellulose. High fiber in it makes this product suitable for health when consumed. This study aims to determine the best treatment that gives the results of quality nata de coco. The experimental design used in this study was Factorial Completely Randomized Design with two treatment factors, namely the first factor comparison between dragon fruit skin extract and coconut water, consisting of five levels of treatment P1 = 5% dragon fruit skin extract: 95% coconut water, P2 = 15% dragon fruit skin extract: 85% coconut water, P3 = 25% dragon fruit skin extract: 75% coconut water, P4 = 35% dragon fruit skin extract: 65% coconut water, P5 = 45% dragon fruit skin extract: 55 % coconut water. The second factor is the boiling temperature, consisting of three levels of treatment S1 = 30ºC, S2 = 40ºC, S3 = 50ºC. Repeat for each treatment combination twice. Observation parameters included thickness of nata, weight of nata, anthocyanin level and fiber content. The results showed that the addition of dragon fruit skin extract had not been able to increase the thickness of the nata, nata weight and nata fiber levels but could increase the level of anthocyanin nata. The highest proportion of thickness, weight and highest levels of nata de coco fiber was obtained in the treatment of 5% dragon fruit skin extract and 95% coconut water. The best proportion with the highest anthocyanin level is in the treatment of 45% dragon fruit skin extract and 55% coconut water. The best boiling temperature is at 300C. Boiling temperature does not affect the thickness of the weight and the fiber content of nata de coco. Boiling temperature significantly affects the anthocyanin level of nata de coco..